Digital Inclusive Finance Empowers the High-Quality Development of County Economies in Shaanxi Province - Xiao, Yangjia (Asia Pacific Economic and Management Review, 2025)
With the vigorous implementation of the national rural revitalization strategy, digital inclusive finance has been practiced in the fields of "agriculture, rural areas, and farmers". It has effectively addressed the issue of financial service exclusion in rural areas, improved the efficiency of financial services in rural regions, and injected vitality into the economic and social development of county areas. As an underdeveloped western province, Shaanxi faces a relative shortage of financial resources, which to a certain extent restricts the development of its county economies. This paper first describes the basic overview of Shaanxi’s county economies, then clarifies the impact mechanism of developing digital inclusive finance on the high-quality development of county economies, and finally analyzes the current development dilemmas of digital inclusive finance in Shaanxi’s counties. Corresponding implementation pathways are proposed to enable digital inclusive finance to better empower the high-quality development of Shaanxi’s county economies in the future.